REWARDS AND PUNISHMENTS GIVEN BY THE TEACHER TO MOTIVATE STUDENTS IN LEARNING ENGLISH AT UPT SMP NEGERI 2 BARANTI - Ridha Sari; St. Asriati AM; Andi Bulkis Maghfirah (FKIP Unismuh Makassar, 2021)
This study intended to investigate (1) The kinds of Reward used by teacher to motivate the students in learning English at UPT SMP Negeri 2 Baranti, (2) The kinds of punishment used by teacher to motivate the students in learning English at UPT SMP Negeri 2 Baranti, (3) The obstacles faced by teacher in motivating students using reward and punishment. This study used a descriptive qualitative method. One of English teacher who teaches in the 8th grade was a participant in this study. The data obtained through an interview consisting of 35 questions, 17 questions about reward and 18 questions about punishment. The Data analysis was carried out by reducing the data, then presenting the data, and after that drawing conclusions and verification. The results have shown that the kinds of reward used by teacher are praise, respect, and sign of appreciation, while the kinds of punishment used by teacher are punishment by action, punishment by word, and corporal punishment. In addition, the obstacles faced by teacher in applying reward was sometimes teacher made mistakes in giving rewards to students causing students protest, while the obstacles that faced by teachers in giving punishment were sometimes difficult determining who was the student who committed the offense, students did not do the punishment well, and students did not pay attention what the teacher said when only given reprimand and if giving punishment too harsh is not allowed